(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The modern business environment is getting more dynamic and complex. This means that good leadership is not only about technical skill but also about objective, emotive, and inspirational abilities. Telling stories has become an increasingly powerful leadership tool. The given paper will focus on the ways in which narrative-based leadership can influence the motivation, cohesion, and performance of the team, particularly in the corporate environment in which the younger professionals are defining the new workplace requirements. The research design is qualitative, with a case-study approach, semi-structured interviews, systematic observations, and analysis of narrative artifacts, and a heterogeneous sample of organizations. It explores the daily use of storytelling as a middle-level management tool, inquiring into its roles in supporting organizational change, reinforcing corporate values, and leading groups through difficult periods. Findings suggest that stories told in a timely manner, authentic, and with emotional appeal, build trust within the team, help them understand their mission, and encourage them to align. Besides, storytelling can help managers overcome generational differences, enhance their leadership capacity, and create a human-oriented team strategy. Although storytelling is not a panacea, the application of this tool to leadership practice has immediate positive effects. The research ends up in practical findings and recommendations about the future leaders in the modern working environment.